Current Knowledge on Porcine circovirus 3 (PCV-3): A Novel Virus With a Yet Unknown Impact on the Swine Industry - Klaumann, Francini; Correa-Fiz, Florencia; Franzo, Giovanni; Sibila, Marina; Núñez, José I.; Segalés, Joaquim (Frontiers in Veterinary Science, 2018)
Porcine circovirus 3 (PCV-3) is a recently described virus belonging to the family Circoviridae. It represents the third member of genus Circovirus able to infect swine, together with PCV-1, considered non-pathogenic, and PCV-2, one of the most economically relevant swine viruses for the worldwide industry. PCV-3 was originally found by metagenomics analyses in 2016 in tissues of swine suffering from porcine dermatitis and nephropathy syndrome, reproductive failure, myocarditis and multisystemic inflammation. The lack of other common pathogens as potential infectious agents of these conditions prompted the suspicion that PCV-3 might etiologically be involved in disease occurrence. Subsequently, viral genome was detected in apparently healthy pigs, and retrospective studies indicated that PCV-3 was already present in pigs by early 1990s. In fact, current evidence suggests that PCV-3 is a rather widespread virus worldwide. Recently, the virus DNA has also been found in wild boar, expanding the scope of infection susceptibility among the Suidae family; also, the potential reservoir role of this species for the domestic pig has been proposed. Phylogenetic studies with available PCV-3 partial and complete sequences from around the world have revealed high nucleotide identity (>96%), although two main groups and several subclusters have been described as well. Moreover, it has been proposed the existence of a most common ancestor dated around 50 years ago. Taking into account the economic importance and the well-known effects of PCV-2 on the swine industry, a new member of the same family like PCV-3 should not be neglected. Studies on epidemiology, pathogenesis, immunity and diagnosis are guaranteed in the next few years. Therefore, the present review will update the current knowledge and future trends of research on PCV-3.